2003
DOI: 10.1002/jbm.b.10035
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term wear of ceramic matrix composite materials for hip prostheses under severe swing phase microseparation

Abstract: The purpose of this study was to evaluate the long-term wear performance of alumina matrix composite (AMC) heads against alumina matrix composite inserts and alumina matrix composite heads against alumina (Al) inserts with the use of a hip-joint simulator incorporating severe swing phase joint microseparation. The wear of AMC on Al produced an average wear rate of 0.61 mm3/million cycles over the 5-million-cycle test duration. The wear of AMC on AMC produced an average wear rate of 0.16 mm3/million cycles over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
75
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 124 publications
(85 citation statements)
references
References 14 publications
5
75
1
Order By: Relevance
“…The smaller grain size in the AMC material may contribute to this difference. This may lead to lesser disruption of the fluid film layer and lessen the risk of squeaking [37,46].…”
Section: Discussionmentioning
confidence: 99%
“…The smaller grain size in the AMC material may contribute to this difference. This may lead to lesser disruption of the fluid film layer and lessen the risk of squeaking [37,46].…”
Section: Discussionmentioning
confidence: 99%
“…Another possible explanation could be the increased joint laxity with a shorter neck length. This may increase the amount of microseparation [2,19,20] and thus be a precursor of the squeaking sound. For instance, increased microseparation makes squeaking as a result of the stickand-slip mechanism more likely [21].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the nature of the femoral head might affect the wear of the polyethylene so a change to ceramic heads [15][16][17][18][19][20][21][22][23][24] was tested and has been instituted in many marketed devices. The use of ceramic-on-ceramic, in which both component materials are replaced by ceramic has also been tested and utilized in surgery [25][26][27][28] for several years. Metal-on-metal articulations initially had been used in the 1960s and 1970s [29,30] and have recently become attractive again as a possible solution to wear problems [22,[31][32][33][34][35][36][37][38].…”
Section: Open Accessmentioning
confidence: 99%